Evaluation of dysphagia at the initial diagnosis of amyotrophic lateral sclerosis. Issue 3 (June 2015) - Murono, Shigeyuki; Hamaguchi, Tsuyoshi; Yoshida, Hiroshi; Nakanishi, Yosuke; Tsuji, Akira; Endo, Kazuhira; Kondo, Satoru; Wakisaka, Naohiro; Yamada, Masahito; Yoshizaki, Tomokazu
Abstract Objective Dysphagia eventually occurs in amyotrophic lateral sclerosis (ALS). Swallowing in patients with ALS at their initial diagnosis was evaluated using videofluoroscopy (VF). Methods Nineteen consecutive patients with ALS, 14 with bulbar symptoms, and 5 without them, underwent VF. Fourteen physiologic components, 6 oral and 8 pharyngeal components, were assessed during the examination. Results Significantly poorer scores were observed in three of the 6 oral components and 3 of the 8 pharyngeal components in patients with bulbar symptoms. Furthermore, bolus transport from the oral cavity to pharynx, pharyngeal constriction, oral residue and pharyngeal residue were impaired in patients even without bulbar symptoms. On the other hand, pharyngoesophageal segment opening was preserved in patients even with bulbar symptoms. Bolus transport and initiation of pharyngeal swallow were correlated with the swallowing category of the ALS severity scale. Conclusion Defining types of impairment in patients with or without bulbar symptoms is useful for evaluating dysphagia in this disease. Although VF showed impairment of oral and pharyngeal phases of swallowing, the oral phase affected the eating habit in ALS at the initial diagnosis.